Pembuatan pupuk organik cair dari bonggol pisang di Greenhouse Universitas Sulawesi Barat sebagai sarana pemberian ilmu bagi mahasiswa: Liquid organic fertilizer production from banana corms in the Greenhouse of Universitas Sulawesi Barat for imparting knowledge to students - Vitha Vitha; Rasdia Rasdia; Darmansa Darmansa; Fachrul Busri; Ahlak Ahlak (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2024)
Using inorganic fertilizers has been proven to increase soil productivity, but excessive use can cause soil and environmental damage. To overcome this problem, liquid organic fertilizer from banana humps can be an alternative solution. This article explains the process of making liquid organic fertilizer from banana corms and its impact on plant growth through community service and practicum activities. Students from the Agroecotechnology Study Program at Greenhouse of the Universitas Sulawesi Barat have successfully produced liquid organic fertilizer. The manufacturing process involves cleaning, cutting, and fermenting banana corms with the addition of brown sugar and rice washing water. The results of this fermentation can improve soil quality and plant productivity with an application method that is quite efficient and environmentally friendly.